2008
DOI: 10.1002/ange.200800918
|View full text |Cite
|
Sign up to set email alerts
|

Bifurkationen auf den Potentialenergiehyperflächen organischer Reaktionen

Abstract: Ein einziger Übergangszustand kann zu mehreren Zwischenstufen oder Produkten führen, wenn sich der Reaktionsweg nach dem Übergangszustand gabelt. Solche Gabelungen (Bifurkationen) entstehen beim Vorliegen sequenzieller Übergangszustände ohne dazwischenliegendem Energieminimum. Die Selektivität dieser Reaktionen wird nicht von der Energetik des Übergangszustands, sondern von der Form der Potentialenergiehyperfläche und von dynamischen Effekten gesteuert. In diesem Kurzaufsatz werden jüngste Untersuchungen von o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 94 publications
0
15
0
1
Order By: Relevance
“…Thermodynamic control would lead to a mixture of internal olefins similar to that of entry 1 in Table 2. [46] The barrier between Fe(2-butyl)-2 and butene adducts HFe(2-E-butene) and HFe(2-Z-butene) is 5.8 and 5.4 kcal mol À1 , respectively. The different behavior of these olefins is shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…Thermodynamic control would lead to a mixture of internal olefins similar to that of entry 1 in Table 2. [46] The barrier between Fe(2-butyl)-2 and butene adducts HFe(2-E-butene) and HFe(2-Z-butene) is 5.8 and 5.4 kcal mol À1 , respectively. The different behavior of these olefins is shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[6c] Für intramolekular angebotene Alkylketten in aromatischen Diinsubstraten wurde eine selektive Aktivierung des bständigen Wasserstoffatoms beobachtet, und es wurden Produkte mit einer Fulventeilstruktur erhalten (Schema 1, oben). Basierend auf den Rechnungen von Zhang et al, die über einen Bifurkationsweg [7] für die Cyclisierung von Diinen berichteten, [6a] wollten wir durch den Einsatz von 2,3-Diethinylthiophenen mit terminaler CC-Bindung als heteroaromatischen Vorstufen den bisher unbekannten 6-endo-digCyclisierungsmodus erreichen; die Zwischenstufe der 5-exodig-Cyclisierung mit der Anellierung von zwei fünfgliedrigen Ringen sollte weniger stabil als die Zwischenstufe der 6-endodig-Cyclisierung mit der Anellierung von einem fünf-und einem sechgliedrigen Ring sein. Dies würde die Mçglichkei-ten der s-p-dualen Aktivierung durch Gold zusätzlich erweitern.…”
unclassified
“…Theoccurrence of post-TS bifurcations in higherorder cycloadditions of ap entafulvene with tropone,a nd nitrostyrene with cyclopentadiene,h ave been documented previously by Houk et al [16] Furthermore,i tw as found that polarizing Lewis acid catalysts altered the potential energy surface to favor the product resulting from nitrostyrene acting as a4 p component. This difference could hint at apreference for pathway D. No concerted TS structures connecting the isobenzofulvenes 6 directly to 10 were found and could be relevant to the discrepancy in diastereoselectivity between experiment and theory.H owever,T Ss tructures (TS-III, Scheme 4) connecting 7 to 10 have been located (pathways Aa nd D).…”
Section: Methodsmentioning
confidence: 57%
“…This data suggests that these two intermediates are at the very least in equilibrium in the reaction mixture.Itispossible that as ingle TS connects 6 and 7,a sw ell as 10,v ia ap ost-TS bifurcation. Theoccurrence of post-TS bifurcations in higherorder cycloadditions of ap entafulvene with tropone,a nd nitrostyrene with cyclopentadiene,h ave been documented previously by Houk et al [16] Furthermore,i tw as found that polarizing Lewis acid catalysts altered the potential energy surface to favor the product resulting from nitrostyrene acting as a4 p component. [16b] Analogously,t he presence of the methoxy substituents in 6c,d,w hich polarizes all structures involved in the proposed pathways,may promote 2a to act as a4 p component.…”
Section: Methodsmentioning
confidence: 69%